2015
DOI: 10.1111/den.12483
|View full text |Cite
|
Sign up to set email alerts
|

OLGA‐ and OLGIM‐based staging of gastritis using narrow‐band imaging magnifying endoscopy

Abstract: Staging of gastritis using NBI-ME approximates that based on histology, and would be a practical alternative to the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 14 publications
1
35
0
5
Order By: Relevance
“…In another study, NBI was compared to the operative link for gastritis assessment and for gastric intestinal metaplasia assessment (OLGA and OLGIM, respectively) staging systems which can separate low‐ and high‐risk groups for gastric cancer (GC). The degree of correspondence between the two methods was 89.1% . Furthermore, NBI enables the sampling of targeted biopsies (“site specific”) vs standard site biopsies; this method was shown to be more effective for both detection of H. pylori and detection of premalignant lesions …”
Section: Invasive Testsmentioning
confidence: 97%
“…In another study, NBI was compared to the operative link for gastritis assessment and for gastric intestinal metaplasia assessment (OLGA and OLGIM, respectively) staging systems which can separate low‐ and high‐risk groups for gastric cancer (GC). The degree of correspondence between the two methods was 89.1% . Furthermore, NBI enables the sampling of targeted biopsies (“site specific”) vs standard site biopsies; this method was shown to be more effective for both detection of H. pylori and detection of premalignant lesions …”
Section: Invasive Testsmentioning
confidence: 97%
“…The diagnostic yield of white-light, chromo, and NBI endoscopy for intestinal metaplasia has been discussed previously [11,19,20]. In white-light endoscopy, villous mucosa and whitish mucosa were indicative of intestinal metaplasia [19].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, narrow-band imaging (NBI) endoscopy is reportedly fairly accurate for the diagnosis of atrophy and intestinal metaplasia [9-11]. In our previous study, the micro-mucosal pattern in the gastric corpus was classified as foveolar or groove type using magnifying NBI endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, taking several biopsy specimens for gastritis staging tends to be avoided. Furthermore, this approach for gastritis staging imposes a considerable burden on endoscopist, pathologist and substantially increases medical costs and procedure time [18] . Taken together these data suggested the importance of real time diagnosis of atrophic gastritis as well as IM and staging of gastric cancer risk, during endoscopic surveillance for gastric precancerous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together these data suggested the importance of real time diagnosis of atrophic gastritis as well as IM and staging of gastric cancer risk, during endoscopic surveillance for gastric precancerous lesions. Recently Saka et al, concluded that staging of gastritis using NBI-magnifying endoscopy is able to approximate that determined by OLGA and OLGIM staging and is expected to be a practical approach that can replace staging based on the histology of biopsy specimen [18] . However examining the whole stomach by NBI-ME is difficult, time consuming, need special patient preparation and not suitable for patients screening.…”
Section: Discussionmentioning
confidence: 99%